Indications and efficacy of conversion from tacrolimus‐ to sirolimus‐based immunosuppression in pediatric patients who underwent liver transplantation for unresectable hepatoblastoma. (4th February 2019) - Hendrickson, Richard J.; Sujka, Joseph; Fischer, Ryan; Manalang, Michelle; Daniel, James; Andrews, Walter S.
Abstract: SRL‐based immunosuppressive strategies in pediatric liver transplantation are not clearly defined, especially within the first year after liver transplant. TAC is the more common, traditional immunosuppressant used. However, SRL may modulate TAC‐associated kidney injury and may also have antiproliferative properties that are valuable in the management of patients following liver transplantation for HB. We sought to determine whether early conversion from TAC to SRL was safe, effective, and beneficial in a subset of liver transplant recipients with unresectable HB exposed to CDDP‐based chemotherapy. Between 2008 and 2013, six patients were transplanted for unresectable HB. All patients received at least one cycle of CDDP‐based chemotherapy prior to transplant. All patients were switched from TAC‐ to SRL‐based immunosuppression within 1 year of transplant. Five patients had improvement in their mGFR, while one patient had a slight decline. The improvement in mGFR was statistically significant. No adverse events were identified. Three patients had BPAR that responded to pulsed steroids. Historical controls showed similar rates of BPAR within the first year after transplant. There were no identified HB recurrences in the follow‐up time period. Conversion from TAC to SRL appears to be safe and effective in this selected group of pediatric liver transplant recipients without adverse reaction or HB recurrences.